Opinion piece: history matters – evidence and proposals for action. Issue 1 (2nd January 2021) - Ilott, Irene; Edmans, Judi
ABSTRACT: This opinion piece aims to encourage national and transnational associations, schools and individuals to act now, to save and celebrate occupational therapy histories. This appeal is based on evidence from (1) searches for the history of education in England in the 1970s and for the start of the profession across the world; (2) examining the websites of five transnational organisations and four national associations for archives and history in contemporary policies; and (3) scanning the scopes and indexes of 18 journals for history and accounts published in 2019. Sadly, little was found. History is not a research priority and rarely mentioned in journal scopes. The reliance on English language information in the public domain is an important limitation of this exploratory study. The proposals include making history mainstream and valuing our heritage as the source of profession specific knowledge and values. History matters and occupational therapists are history makers.